Challenges of research in rural poverty: lessons from large field surveys. Issue 5 (4th July 2018) - Cheema, Abdur Rehman; Mehmood, Abid; Khan, Fazal Ali
ABSTRACT: This practical note highlights lessons learnt during the data collection of two large field surveys as part of the ongoing "Sindh Union Council and Economic Strengthening Support" (SUCCESS) programme in southern Pakistan. The experience is discussed in terms of language barriers, the educational status of households, dealing with people's expectations and non-cooperation, and the weather conditions. The note also highlights the practice of public sharing of data in real-time to improve the design and implementation of future surveys, especially those measuring poverty and quality of life.